AB0521 Safety, pharmacokinetics, and pharmacodynamics of single doses of a bispecific icosl and baff inhibitor, amg 570, in healthy subjects - Cheng, L.E.; Kankam, M.; Siebers, N.; Stoltz, R.; Abuqayyas, L.; Ertik, B.; Sullivan, B.A.; Zhou, L.; Mitragotri, D.; Parnes, J.R. (Annals of the rheumatic diseases, 2018)
BackgroundAutoimmune diseases, including systemic lupus erythematosus (SLE), are associated with dysregulation in both T cell and B cell responses. Targeting the activity of both cell types simultaneously holds promise as a treatment for autoimmune disease. AMG 570 is a bispecific molecule targeting both T cell and B cell activity through neutralisation of the inducible costimulator ligand (ICOSL) and the B cell activating factor (BAFF).ObjectivesTo investigate the safety, tolerability, pharmacokinetics, and pharmacodynamics of AMG 570 in healthy subjects after single subcutaneous doses.MethodsThis ongoing, double-blind, randomised, placebo-controlled trial has enrolled healthy subjects (age ≥18 years) into escalating single-dose cohorts. Eight participants were enrolled into each cohort and were randomised 3:1 to receive either AMG 570 or placebo across six cohorts of increased dose level. The primary endpoint of the study was treatment-emergent adverse events (AEs). Secondary endpoints included pharmacokinetics and pharmacodynamics (eg, receptor occupancy of ICOSL, changes in B cell subpopulations, and serum immunoglobulin levels).ResultsAs of an ad hoc interim analysis on October 5, 2017, 48 participants were enrolled and received one dose of investigational product (either AMG 570 or placebo). 73 AEs were reported; all were mild (n=56) to moderate (n=14) in severity (3 injury AEs had no grade reported). Upper respiratory tract infection and injection site erythema were the most commonly reported AEs. No drug-related serious adverse events were reported. No severe, life-threatening, or fatal AEs were reported. AMG 570 demonstrated nonlinear pharmacokinetics consistent with cell surface target (ICOSL) interaction. In the highest dose tested, AMG 570 achieved greater than 90% mean ICOSL receptor occupancy on circulating B cells 8 days after dosing, and high levels (>85% mean ICOSL receptor occupancy) were observed 29 days after dosing. AMG 570 led to a reduction in circulating naïve B cells and an increase in circulating memory B cells. No apparent changes were observed in serum IgM or IgG.ConclusionsOverall, AMG 570 was safe and well tolerated by healthy subjects. AMG 570 demonstrated pharmacodynamic activity consistent with ICOSL and BAFF neutralisation.Disclosure of InterestL. Cheng Shareholder of: Amgen Inc., Employee of: Amgen Inc., M. Kankam: None declared, N. Siebers: None declared, R. Stoltz: None declared, L. Abuqayyas Shareholder of: Amgen Inc., Employee of: Amgen Inc., B. Ertik Shareholder of: Amgen Inc., Employee of: Amgen Inc., B. Sullivan Shareholder of: Amgen Inc., Employee of: Amgen Inc., L. Zhou Shareholder of: Amgen Inc., Employee of: Amgen Inc., D. Mitragotri Shareholder of: Amgen Inc., Employee of: Amgen Inc., J. Parnes Shareholder of: Amgen Inc., Employee of: Amgen Inc.